2019
DOI: 10.1002/jsfa.9953
|View full text |Cite
|
Sign up to set email alerts
|

Content and bioavailability of trace elements and nutrients in grape pomace

Abstract: BACKGROUND The possible agricultural use of grape pomace could be limited by the content and mobility of metals. This is influenced by many factors. In this study, the abundance and availability of heavy metals and essential nutrients were evaluated comprehensively in different grape pomace residues from winemaking of five white and red grape varieties, before and after the distillation process. RESULTS The total metal content found in grape pomace skins and seeds confirmed that there was greater metal accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
1
10
1
Order By: Relevance
“…The metal content of GP skins is reported in Table 3 and shows that K is the most abundant metal in all varieties analyzed; similar findings have been reported by Pérez Cid et al ( 2019 ) for grape skins isolated from the pomace of five Galician grape varieties.…”
Section: Discussionsupporting
confidence: 86%
“…The metal content of GP skins is reported in Table 3 and shows that K is the most abundant metal in all varieties analyzed; similar findings have been reported by Pérez Cid et al ( 2019 ) for grape skins isolated from the pomace of five Galician grape varieties.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, the amounts of Se, Mn, and Zn in GS powder reached 2, 2, and 1 mg/kg, respectively. These results are quite different from the Se content of grapes reported in the literature [27][28][29], which may be related to the grape species studied and their different origins. Depending on the contents of minerals and trace elements in GSKs and GSs, different processing methods can be considered.…”
Section: Resultscontrasting
confidence: 99%
“…Few studies reported the presence of heavy metals in the whole grape pomace [ 27 , 28 ], with values (mg/kg DM) averaging 111 for Al [ 28 ], 16.3 for Pb, 3.5 for Ni, and 1.1 for Cd [ 27 ]. Indeed, most reports analyzed the accumulation of trace elements in grape stem [ 27 , 29 ], skin [ 30 , 31 , 32 ], or seed [ 26 , 32 ]. There is a great variability in heavy metal contents in grape by-products, since they depend on soil composition and contamination and on the grape genetic variety.…”
Section: Nutritional Properties Of Grape By-products and Strategies T...mentioning
confidence: 99%
“…There is a great variability in heavy metal contents in grape by-products, since they depend on soil composition and contamination and on the grape genetic variety. For instance, 8.1 mg/kg DM of Al and 0.002 mg/kg DM of Pb was found in grape skin in the study from De Nisco et al [ 30 ], but other grape varieties could accumulate 158–575 mg/kg DM of Pb in their skins [ 32 ]. However, in grape stem and seed, the predominant trace element was Al (average of 201 and 0.78 mg/kg DM, respectively) ( Table 2 ).…”
Section: Nutritional Properties Of Grape By-products and Strategies T...mentioning
confidence: 99%
See 1 more Smart Citation